2012
DOI: 10.1371/journal.pntd.0001993
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation and Impact on Clinical Management of a Rapid Diagnostic Kit That Detects Dengue NS1, IgM and IgG

Abstract: BackgroundDengue diagnosis is complex and until recently only specialized laboratories were able to definitively confirm dengue infection. Rapid tests are now available commercially making biological diagnosis possible in the field. The aim of this study was to evaluate a combined dengue rapid test for the detection of NS1 and IgM/IgG antibodies. The evaluation was made prospectively in the field conditions and included the study of the impact of its use as a point-of-care test for case management as well as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
86
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 22 publications
14
86
2
2
Order By: Relevance
“…21,23 Guzman and others 8 also reported lower sensitivity of NS1 antigen detection in American countries (Nicaragua and Venezuela) compared with Asian countries. 8,24 The occurrence of secondary infections also seems to have an impact on the accuracy of IgM detection. Indeed, higher sensitivity of the anti-IgM SD Bioline Dengue Duo was evidenced in primary DENV infections compared with secondary infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,23 Guzman and others 8 also reported lower sensitivity of NS1 antigen detection in American countries (Nicaragua and Venezuela) compared with Asian countries. 8,24 The occurrence of secondary infections also seems to have an impact on the accuracy of IgM detection. Indeed, higher sensitivity of the anti-IgM SD Bioline Dengue Duo was evidenced in primary DENV infections compared with secondary infections.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies evidenced that the diagnostic performances of different dengue diagnosis kits vary depending on geographical and temporal factors. 8,22,24,27 Thus, validation of those kits in one country should take into account 1) the epidemiological settings (endemic, epidemic, and hyperepidemic periods), 2) the genetic background and immunological status of studied population, the different phases of the dengue disease, and 3) the DENV serotypes and genotypes that are circulating in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Thus a centrally validated (CDC) and widely accepted ELISA method is helpful for use as a comparator to assess rapid ICT assays. 12,13 Some studies have shown high rates of sensitivity and specificity for rapid ICT assays. 9 However, in the current study, the sensitivity and the NPV for anti-dengue virus IgM detection by the rapid ICT assay were comparatively lower than that of ELISA (Table 2) with the inference that this particular assay will give a high percentage of false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…According to the special surveillance of Bsummer fevers^in Veneto region, Northern Italy, every febrile (≥38°C) traveller recently returned from endemic countries, after malaria and other obvious causes of fever have been ruled out, is considered as a possible case of DENV or CHIKV [88]. For DENV, RDT with good sensitivity and specificity are available [89]: in case of positivity, the patient is considered a probable case and samples are sent to a referral laboratory for confirmation (PCR and viral isolation). Unfortunately, an antigen RDT is not available for CHIKVand the sensitivity of RDT (for detection of IgM and IgG) is poor, especially during the first few days of fever.…”
Section: Surveillance In Non-endemic Areasmentioning
confidence: 99%